(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Employees are one of the main priorities for many organizations. High work productivity is greatly influenced by various factors, one of which is the quality of leadership and work culture within the team. This study aims to analyze the effect of participative leadership and collaborative teams on work productivity, with job satisfaction as an intervening variable on employees of PT Maha Putra Engineering. This study combines participative leadership and cooperation time as independent variables, with job satisfaction as an intervening variable to analyze work productivity. This study uses a quantitative approach, which aims to measure and analyze the relationship between variables that have been determined systematically and objectively. The population used in this study was 96 employees, the sample in this study was the entire sample of 96 employees. The data analysis technique used was the Patrial Least Square (PLS) using Smart PLS software. The results of this study indicate that participative leadership has a positive and significant effect on productivity and work satisfaction, as well as work productivity through job satisfaction as an intervening variable (partial). Working time has a positive and significant effect on job satisfaction, and work productivity through job satisfaction as an intervening variable (full), but does not directly affect work productivity. The findings of this study provide new insights into the importance of job satisfaction as a relationship in the influence of working time on productivity as well as the conditions, organizational culture, and leadership dynamics in working time in companies must be more focused and relevant to the company.